A study of factors effecting employee performance management at Hotel Equatorial Melaka, Bandar Hilir Melaka / Nurfarahanna Najwa Mohd Yunos - Mohd Yunos, Nurfarahanna Najwa (Faculty of Business and Management, 2019)
This study aims to identify the factors effecting employee. The study was conducted in Hotel Equatorial Melaka in Bandar Hilir Melaka Bandaraya Bersejarah. Quantitative method was used and five types of Likert-Scale questionnaire was distribute to respondent. There are 200 sets of questionnaires were prepared and distributed to the targeted respondents who are working in the hotel industry of Hotel Equatorial Melaka. It is to clarify each of elements in the questionnaire to gain the most efficient result on this research. Performance management is an asset of each organization in this world. It is a value of human capital in which to determine whether it is an effective way to increase mobility of the employee itself in achieving organization objectives. Somehow, some organization is not able to practice effective employee performance management method. As we all know, the communication basic components starts from sender, channel, massage, receiver, and noise. It could be related to how it is affecting an employee from being unsupervised. As it happen in many company, the main issue of effective performance management were caused from miss-communication. When both side, which is employer and employee cannot have clear statement of information that could verify from what they heard from other people about something much important and it could affect their understanding and that is why either employer or employee should practice face to face communication to avoid employer under-value their employees performance in anything that lead supervisor to underestimate the employee. Performance management is the process where a business uses to assess its employees plus to determine the efficiency of its activity in achieving organization objectives. It includes completing a task of planning new business actions, and monitors the progress of actions and examines and brings the business closer to its goals. This research is to identify the effect when communication breakdown occur in organization that affect employee performance management. The major findings, limitations for the study, implications of the study and recommendations of this study will be discussed.